Immunotoxicity assessment of cadinene sesquiterpenes from Eupatorium adenophorum in mice - Can-bin OUYANG; Xiao-man LIU; Dong-dong YAN; Yuan LI; Qiu-xia WANG; Ao-cheng CAO; mei-xia GUO (Journal of Integrative Agriculture)
Sesquiterpenes in Eupatorium adenophorum are abundant in leaves and have great development potential as biopesticides. The toxicity of sesquiterpenes in immune cells and their corresponding immune functions are not fully understood. We evaluated the immunotoxicity of two cadinene sesquiterpenes 2-deoxo-2-(acetyloxy)-9-oxoageraphorone (DAOA) and 9-oxo-10,11-dehydro-agerophorone (ODA) by using histopathology and toxicology methods in vitro and in vivo in lymphocytes and natural killer cells in Kunming mice. The mice were given single doses of 75, 150 and 300 mg kg−1 body weight (BW) of DAOA/ODA every day for a week. Serious damage to the thymus and spleen was found in tissue images with clear lysis reduction numbers and a loosened arrangement of splenocytes and thymocytes to the mice treated with 150–300 mg kg−1 DAOA/ODA. Mice cytology was also affected with significant cellular alterations, increased splenocytes apoptosis rates (P<0.01), proliferation reduction (P<0.05) and natural killer cells activities reduction (P<0.05) when given 150–300 mg kg−1 DAOA/ODA, the severities of which were dose-dependent. However, a 75 mg kg−1 dose of DAOA/ODA showed no change in tissue or cytology after the 7 day treatment, and therefore was considered to be within acceptable safety parameters. Taken together, cadinene sesquiterpenes, as a type of toxic botanical component, have low environmental risks in small doses and should be further studied for their use as biopesticides.